Pellet diameter of Ganoderma lucidum in a repeated-batch fermentation for the trio total production of biomass-exopolysaccharide-endopolysaccharide and its anti-oral cancer beta-glucan response - Abdullah, Nur Raihan; Sharif, Faez; Azizan, Nur Hafizah; Mohd Hafidz, Ismail Fitri; Supramani, Sugenendran; Ahmad Usuldin, Siti Rokhiyah; Ahmad, Rahayu; Wan-Mohta, Wan Abd Al Qadr Imad (AIM Press, 2020)
The pellet morphology and diameter range (DR) of Ganoderma lucidum were observed in a repeated-batch fermentation (RBF) for the trio total production of biomass, exopolysaccharide (EPS) and endopolysaccharide (ENS). Two factors were involved in RBF; broth replacement ratio (BRR: 60%, 75% and 90%) and broth replacement time point (BRTP: log, transition and stationary phase) in days. In RBF, 34.31 g/L of biomass favoured small-compact pellets with DR of 20.67 μm< d < 24.00 μm (75% BRR, day 11 of BRTP). EPS production of 4.34 g/L was prone to ovoid-starburst pellets with DR of 34.33 μm< d <35.67 μm (75% BRR, day 13 of BRTP). Meanwhile, the highest 2.43 g/L of ENS production favoured large-hollow pellets with DR of 34.00 μm< d < 38.67 μm (90% BRR, day 13 of BRTP). In addition, RBF successfully shortened the biomass-EPS–ENS fermentation period (31, 33 and 35 days) from batch to 5 days, in seven consecutive cycles of RBF. In a FTIR detection, β- 380 AIMS Microbiology Volume 6, Issue 4, 379–400. glucan (BG) from EPS and ENS extracts were associated with β-glycosidic linkages (2925 cm-1, 1635 cm-1, 1077 cm-1,920 cm-1 and 800 cm-1 wavelengths) with similar 1H NMR spectral behaviour (4.58, 3.87 and 3.81). Meanwhile, 4 mg/L of BG gave negative cytotoxic effects on normal gingival cell line (hGF) but induced antiproliferation (IC50 = 0.23 mg/mL) against cancerous oral Asian cellosaurus cell line (ORL-48). Together, this study proved that G. lucidum mycelial pellets could withstand seven cycles of long fermentation condition and possessed anti-oral cancer beta-glucan, which suits large-scale natural drug fermentation.